2014
DOI: 10.1371/journal.pone.0102093
|View full text |Cite
|
Sign up to set email alerts
|

miR-485-5p Binding Site SNP rs8752 in HPGD Gene Is Associated with Breast Cancer Risk

Abstract: BackgroundSingle nucleotide polymorphisms (SNPs) that reside in microRNA target sites may play an important role in breast cancer development and progression. To reveal the association between microRNA target site SNPs and breast cancer risk, we performed a large case-control study in China.MethodsWe performed a two-stage case-control study including 2744 breast cancer cases and 3125 controls. In Stage I, we genotyped 192 SNPs within microRNA binding sites identified from the “Patrocles” database using custom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…For instance, hsa‐mir‐485‐5p can reverse epithelial to mesenchymal transition and promote cisplatin‐induced cell death via targeting P21 (RAC1) activated kinase 1 (PAK1) in oral tongue squamous cell carcinoma . Hsa‐mir‐485‐5p–binding site single‐nucleotide polymorphism rs8752 in the 15‐hydroxyprostaglandin dehydrogenase (HPGD) gene is correlated with the risk of breast cancer . However, its cellular function in NSCLC is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, hsa‐mir‐485‐5p can reverse epithelial to mesenchymal transition and promote cisplatin‐induced cell death via targeting P21 (RAC1) activated kinase 1 (PAK1) in oral tongue squamous cell carcinoma . Hsa‐mir‐485‐5p–binding site single‐nucleotide polymorphism rs8752 in the 15‐hydroxyprostaglandin dehydrogenase (HPGD) gene is correlated with the risk of breast cancer . However, its cellular function in NSCLC is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…40 Hsa-mir-485-5p-binding site single-nucleotide polymorphism rs8752 in the 15-hydroxyprostaglandin dehydrogenase (HPGD) gene is correlated with the risk of breast cancer. 41 However, its cellular function in NSCLC is not clear. Consistent with the roles of hsa-mir-485-5p in other cancers, we found that hsa-mir-485-5p was decreased in serum samples from NSCLC patients and NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNAsnp (http://rth.dk/resources/ rnasnp/submit) is a web-based tool which enables the prediction of structural changes induced by SNPs (Sabarinathan et al, 2013). These freely available databases and tools may support the study of functional changes associated with miRNA variants and have supported several studies to date (He et al, 2014b;Li et al, 2014;Swart and Dandara, 2014). The Collaborative Oncological Gene-environment Study assessed the association of 767 MirSNPs and EOC risk in 18,174 EOC cases and 26,134 controls.…”
Section: Mirsnps In the Binding Sites Of Target Genes Impact On Ovarimentioning
confidence: 99%
“…Afterward numerous investigations have revealed the SNPs within miRNA-binding region may contribute to cancer risk and outcomes by altering miRNA-mRNA binding affinities and miRNA-targeted gene expression [7, 8]. For example, He et al found that rs8752 located with miR-485-5p -binding site of HPGD gene was related to the risk of breast cancer [9]. Zhang et al found that miR-367 -binding site rs1044129 in RYR3 gene was associated with poor survival of patients with breast cancer [10].…”
Section: Introductionmentioning
confidence: 99%